Complete Androgen Insensitivity Syndrome: A Rare Case of Disorder of Sex Development - Alfonsa Pizzo; Antonio Simone Laganà; Irene Borrielli; Nella Dugo (Case Reports in Obstetrics and Gynecology)
Androgen Insensitivity Syndrome (AIS) could be considered as a disease that causes resistance to androgens actions, influencing both the morphogenesis and differentiation of the body structures, and systems in which this hormone exerts its effects. It depends on an X-linked mutations in the Androgen Receptor (AR) gene that express a variety of phenotypes ranging from male infertility to completely normal female external genitalia. The clinical phenotypes of AIS could vary and be classified into three categories, as complete (CAIS), partial (PAIS), and mild (MAIS) forms, according to the severity of androgen resistance. We will describe a case of CAIS in a 16-year-old patient.